Kinerja dan Karakteristik Tenaga Kependidikan di Madrasah Tsanawiyah (MTs) Negeri 1 Bantul - Setiawan, Farid; Ubaidillah, Ikhsan; Suryawan, Anggi; Anshori, Muhammad Maulidan; Lutfiana, Annisa (MASALIQ, 2021)
In managing and carrying out various activities in schools, management is needed for each section. As a forum for learning and teaching science, school management is considered very influential on the success of an institution in its implementation. Management, or the effective use of existing resources to achieve goals, is one of the keys to managing an institution. Educational staff are an important part of schools that have responsibility for administrative management, planning school/madrasah activities for 1 year, inputting student data, checking the availability of infrastructure to support learning, checking the completeness of books in the library, and others. Therefore, the optimization of Education Personnel is needed and developed progressively in order to realizing optimal performance and quality in order to achieve school goals.